1995
DOI: 10.1080/14640749508401419
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Disagreement in Object Naming

Abstract: Two experiments examined the processing of objects with low name agreement. Experiment I compared naming latencies for objects with three different types of name disagreement to those for matched control objects with very high name agreement. Objects with low name agreement due to abbreviations (e.g. phone) were named no more slowly than were control objects. Objects with multiple names (e.g. couch, sofa, settee) and objects often given incorrect names (e.g. spider for ant) took longer to name correctly than d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
160
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(213 citation statements)
references
References 15 publications
35
160
2
1
Order By: Relevance
“…This held for object and action pictures alike. NA effects on RTs have been observed in several earlier studies (e.g., Alario and Ferrand, 1999;Barry et al, 1997;Vitkovitch and Tyrrell, 1995). As discussed in Section 1, pictures can differ in NA for a number of reasons.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…This held for object and action pictures alike. NA effects on RTs have been observed in several earlier studies (e.g., Alario and Ferrand, 1999;Barry et al, 1997;Vitkovitch and Tyrrell, 1995). As discussed in Section 1, pictures can differ in NA for a number of reasons.…”
Section: Discussionmentioning
confidence: 67%
“…As discussed in Section 1, pictures can differ in NA for a number of reasons. Specifically, low NA may arise because speakers misidentify objects, or use either abbreviations or full forms, or because they need to select among several appropriate names activated by the depicted objects (Vitkovitch and Tyrrell, 1995). Since the participants in our study were thoroughly familiarized with the pictures before the main experiment, the NA effect in our study likely arose because the selection of the picture names was hindered by the simultaneous activation of several candidate names in the low NA condition.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The fact that many Hom-LF items had near-synonyms could by itself slow down the naming of those Hom-LF pictures, compared to Hom-HF pictures. Several studies showed that objects with low name agreement take longer to name than objects with high name agreement (Lachman, 1973;Lachman, Shaffer, & Hennrikus, 1974;Vitkovitch & Tyrell, 1995). In the case of the Hom-LF items, the situation is more extreme because the Hom-LF names had more dominant counterparts (e.g., slot in the meaning of ''castle'' has a higher frequency counterpart kasteel with a very similar meaning).…”
Section: Resultsmentioning
confidence: 99%